Surface and Interface Chemistry in Colloidal Quantum Dots for Solar Applications Studied by X‐Ray Photoelectron Spectroscopy. Issue 7 (2nd November 2018) - Clark, Pip C. J.; Flavell, Wendy R.
Abstract: Control of the surface and interface chemistry of colloidal quantum dots (CQDs) is critical to achieving a product with good air stability and high performing optoelectronic devices. Through various surface passivation treatments, vast improvements have been made in fields such as CQD photovoltaics; however devices have not currently reached commercial standards. We show how X‐ray photoelectron spectroscopy (XPS) can provide a better understanding of exactly how surface treatments act on CQD surfaces, and the effect of surface composition on air stability and device performance.. We illustrate this with PbS‐based CQDs, using XPS to measure oxidation processes, and to quantify the composition of the topmost surface layer after different surface treatments. We also demonstrate the use of synchrotron radiation‐excited depth‐profiling XPS, a powerful technique for determining the surface composition, chemistry and structure of CQDs. This review describes our recent progress in characterization of CQD surfaces using SR‐excited depth profiling XPS and other photoemission techniques. Abstract : In this account we discuss photoemission techniques for characterizing the surfaces of colloidal quantum dots and nanoparticles, and how synchrotron radiation‐excited depth‐profiling XPS can expand our understanding of nanoparticle surface stability and its effects on device performance. We illustrate the application of this technique to understanding oxidation mechanisms and passivation treatments.